Formulasi Sediaan Lip Cream Ekstrak Etanol Daun Bayam Merah (Amaranthus tricolor L.) Sebagai Pewarna Alami - Muhammad Arif; Tri Nova Lovena; Nurbaiti; Rahmatul Husna (JURNAL FARMASI DAN MAKANAN, 2026)
Lip cream is widely used as a lip color because lip cream can provide an even and long-lasting color. Red spinach contains anthocyanins which function as antioxidants. The lifestyle patterns of people who are starting to return to the back to nature lifestyle are one of the backgrounds for research to formulate lip cream preparations from natural dyes from red spinach (Amaranthus tricolor L.). This study aims to provide information on the use of red spinach as a natural dye. The study was conducted experimentally, including the manufacture of lip cream formulations with red spinach ethanol extract at concentrations of 15% and 17%. Examination of the physical quality of the preparations included organoleptic tests, stability, homogeneity, pH, adhesion, spreadability, irritation, and hedonic tests calculated using SPSS. The results showed that all preparations had good organoleptics, good stability, met the requirements of the homogeneity test, and the appropriate pH. In addition, the preparations also met the adhesion and spreadability tests, and did not cause irritation. The most popular formula is F2 formula with 17% concentration of red spinach ethanol extract, which shows the best performance in these aspects. This study shows the potential of red spinach as a safe and effective natural colorant in lip cream formulation.